The Role of Educational Leader: The Practices and Perceptions of Educational Leaders in Four Early Childhood Education and Care Settings in Western Australia - Bodger, Caryn-Lee (Curtin University, 2020)
The Australian Children’s Education and Care Quality Authority describes the Educational Leader as influential, extending the pedagogy of educators (ACECQA, 2019). However the lack of specific guidelines for the Educational Leader position has resulted in uncertainty. The qualitative research study explores the practices and perceptions of four Western Australian Educational Leaders. The research findings are significant to the early childhood education and care sector by promoting dialogue about how the Educational Leaders themselves are interpreting their role.